2004
DOI: 10.1002/j.2161-1874.2004.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Addictions Counselors' Credibility: The Impact of Interactional Style, Recovery Status, and Nonverbal Behavior

Abstract: The impact of addictions counselors' interactional style (confrontational vs. motivational), recovery status (recovering vs. nonrecovering), and nonverbal behavior (facilitative vs. neutral) on 116 clients' perceptions of addictions counselor credibility was examined in a fully crossed factorial design. Significant results were found, and implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
(57 reference statements)
1
10
0
1
Order By: Relevance
“…The one interview based qualitative study reports on the challenges faced by recovering counsellors' dilemmas, as they maintain dual relationships, by virtue of being an ex-addict and coming in contact with clients that the counsellor is familiar with either through former using days, or from attending 12-step meetings [29]. The other three European survey based studies examine the influence of relating recovery status to the counsellor's sensitivity to ethical dilemmas [30], the impact of addiction counsellor's interactional style [31] and the effectiveness of former alcoholics as association workers in specialized addiction medicine structures [32].…”
Section: Introductionmentioning
confidence: 99%
“…The one interview based qualitative study reports on the challenges faced by recovering counsellors' dilemmas, as they maintain dual relationships, by virtue of being an ex-addict and coming in contact with clients that the counsellor is familiar with either through former using days, or from attending 12-step meetings [29]. The other three European survey based studies examine the influence of relating recovery status to the counsellor's sensitivity to ethical dilemmas [30], the impact of addiction counsellor's interactional style [31] and the effectiveness of former alcoholics as association workers in specialized addiction medicine structures [32].…”
Section: Introductionmentioning
confidence: 99%
“…He quotes one author English (1987) who "found that clients' perceived addiction counsellors with a history from addiction as more expert, attractive and trustworthy" (p. 46) however (Toriello, 2004) found no effect. Thombs and Osborn however made the point that "recovering addiction counsellors did not endorse the CI approach significantly more often than the MI approach" (p. 46), the author considers this surprising given the number of recovering addicts in the field in the field.…”
Section: Preliminary Literature Reviewmentioning
confidence: 99%
“…In the learning of professionalisation for the addiction field there are readily accessible vocabularies that construct and perpetuate a caricatured stereotypical view of the 12 step practioners. For example, they are constructed as being more inherently confrontational than motivational, despite evidence that this is more of a caricature (Toriello, 2004). Newer strength based practices are privileged and welcomed into the new vocabulary yet they are based less on old Freudian and Christian cathartic ideas that release subjectivity (the truth shall set you free) but more on the production of subjectivities conducive to a neo-liberal environment.…”
Section: Hidden Curriculummentioning
confidence: 99%
“…Counselors of this caliber would be outstanding role models as recovery coaches in communities in and of recovery. Modern research continues to identify the strengths of CIRs in terms of equal ability with other counselors to promote credibility with clients and of the superior credibility in their familiarity of 12-Step programs (Dennis, Roland, & Loneck, 2013;Toriello & Stohmer, 2004). These qualities would enhance the effectiveness of CIRs as community coaches.…”
Section: Introductionmentioning
confidence: 99%